Phosphorous Application Improves Drought Tolerance of Phoebe zhennan - Tariq, Akash; Pan, Kaiwen; Olatunji, Olusanya A.; Graciano, Corina; Li, Zilong; Sun, Feng; Sun, Xiaoming; Song, Dagang; Chen, Wenkai; Zhang, Aiping; Wu, Xiaogang; Zhang, Lin; et al. (Frontiers in Plant Science, 2017)
Phoebe zhennan (Gold Phoebe) is a threatened tree species in China and a valuable and important source of wood and bioactive compounds used in medicine. Apart from anthropogenic disturbances, several biotic constraints currently restrict its growth and development. However, little attention has been given to building adaptive strategies for its conservation by examining its morphological and physio-biochemical responses to drought stress, and the role of fertilizers on these responses. A randomized experimental design was used to investigate the effects of two levels of irrigation (well-watered and drought-stressed) and phosphorous (P) fertilization treatment (with and without P) to assess the morphological and physio-biochemical responses of P. zhennan seedlings to drought stress. In addition, we evaluated whether P application could mitigate the negative impacts of drought on plant growth and metabolism. Drought stress had a significant negative effect on the growth and metabolic processes of P. zhennan. Despite this, reduced leaf area, limited stomatal conductance, reduced transpiration rate, increased water use efficiency, enhanced antioxidant enzymes activities, and osmolytes accumulation suggested that the species has good adaptive strategies for tolerating drought stress. Application of P had a significant positive effect on root biomass, signifying its improved water extracting capacity from the soil. Moreover, P fertilization significantly increased leaf relative water content, net photosynthetic rate, and maximal quantum efficiency of PSII under drought stress conditions. This may be attributable to several factors, such as enhanced root biomass, decreased malondialdehyde content, and the up-regulation of chloroplast pigments, osmolytes, and nitrogenous compounds. However, P application had only a slight or negligible effect on the growth and metabolism of well-watered plants. In conclusion, P. zhennan has a strong capability for drought resistance, while P application facilitates and improves drought tolerance mostly through physio-biochemical adjustments, regardless of water availability. It is imperative to explore the underlying metabolic mechanisms and effects of different levels of P fertilization on P. zhennan under drought conditions in order to design appropriate conservation and management strategies for this species, which is at risk of extinction.